2001
DOI: 10.1093/ije/30.5.1119
|View full text |Cite
|
Sign up to set email alerts
|

Education, lifestyle factors and mortality from cardiovascular disease and cancer. A 25-year follow-up of Swedish 50-year-old men

Abstract: These data indicate that modifiable lifestyle factors mediate the inverse gradient between education and death from cerebro- and cardiovascular disease. Smoking, physical activity and dietary factors explained half of the excess cancer mortality in lower educated groups. Further studies are needed to explore the proposed association between palmitoleic acid, a marker of high intake of animal and dairy fat, and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
2
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 38 publications
5
101
2
5
Order By: Relevance
“…An alternative is to develop public health policy prevention programmes. Aspects of socioeconomic status such as occupation, 3 educational attainment, 4 and income; 5 lifestyle factors such as smoking, 6 adverse dietary habits, 7 and physical inactivity; 8 and overweight 9 are associated with CHD. Evaluation of the contribution of each of these factors to the high risk of CHD in the population would help focus the policies and interventions for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is to develop public health policy prevention programmes. Aspects of socioeconomic status such as occupation, 3 educational attainment, 4 and income; 5 lifestyle factors such as smoking, 6 adverse dietary habits, 7 and physical inactivity; 8 and overweight 9 are associated with CHD. Evaluation of the contribution of each of these factors to the high risk of CHD in the population would help focus the policies and interventions for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…First, controlled secondary prevention trials have reported protective effects of increased ALA intake 41,42 or a trend toward decreased CVD risk in women. 40 A recent meta-analysis also reported a nonsignificant trend toward lower CVD risk at higher levels of ALA biomarkers. 43 Second, ALA in serum CE seems to be a weaker biomarker of dietary intake compared with LA, EPA, and DHA, as reported in Swedish men who were investigated during the same time period as in the present study.…”
mentioning
confidence: 97%
“…11 13 [17][18][19][20] Evidence is also accruing that educated men and women in the developing world have lower mortality, but the mechanisms underlying this association are not fully understood. [7][8][9] Understanding social inequalities in developing countries may require looking into the independent effects of individuals within households over and above those between households, partly because women's and men's roles within a household are so distinct.…”
mentioning
confidence: 99%